Fatty Acid Oxidation Is Required for Myxococcus xanthus Development - Bullock, Hannah A. (J Bacteriol, 2018)
Myxococcus xanthus cells produce lipid bodies containing triacylglycerides during fruiting body development. Fatty acid β-oxidation is the most energy-efficient pathway for lipid body catabolism. In this study, we used mutants in fadJ (MXAN_5371 and MXAN_6987) and fadI (MXAN_5372) homologs to examine whether β-oxidation serves an essential developmental function. These mutants contained more lipid bodies than the wild-type strain DK1622 and 2-fold more flavin adenine dinucleotide (FAD), consistent with the reduced consumption of fatty acids by β-oxidation. The β-oxidation pathway mutants exhibited differences in fruiting body morphogenesis and produced spores with thinner coats and a greater susceptibility to thermal stress and UV radiation. The MXAN_5372/5371 operon is upregulated in sporulating cells, and its expression could not be detected in csgA, fruA, or mrpC mutants. Lipid bodies were found to persist in mature spores of DK1622 and wild strain DK851, suggesting that the roles of lipid bodies and β-oxidation may extend to spore germination. IMPORTANCE Lipid bodies act as a reserve of triacylglycerides for use when other sources of carbon and energy become scarce. β-Oxidation is essential for the efficient metabolism of fatty acids associated with triacylglycerides. Indeed, the disruption of genes in this pathway has been associated with severe disorders in animals and plants. Myxococcus xanthus, a model organism for the study of development, is ideal for investigating the complex effects of altered lipid metabolism on cell physiology. Here, we show that β-oxidation is used to consume fatty acids associated with lipid bodies and that the disruption of the β-oxidation pathway is detrimental to multicellular morphogenesis and spore formation.